The impact of sex ratios before marriage on household saving in two Asian countries: The competitive saving motive revisited - Charles Yuji Horioka; Akiko Terada-Hagiwara (Asian Development Bank (ADB), 2016)
This paper estimates a household saving rate equation for India and the Republic of Korea using longterm time series data for the 1975-2010 period, focusing in particular on the impact of the premarital sex ratio on the household saving rate. To summarize the main findings of the paper, it finds that the premarital sex (or gender) ratio (the ratio of males to females) has a significant impact on the household saving rate in both India and the Republic of Korea, even after controlling for the usual suspects such as the aged and youth dependency ratios and income. It has a negative impact in India, where the bride's side has to pay substantial dowries to the groom's side at marriage, but a positive impact in the Republic of Korea, where, as in the People's Republic of China, the groom's side has to bear a disproportionate share of marriage-related expenses including purchasing a house or condominium for the newlywed couple.
Keywords: D12; D14; D91; E21; J11; J12; O16; 330; age structure of the population; competitive saving motive; dowries; gender ratio; household saving rate; India; life cycle hypothesis; marriage expenses; population control; premarital sex ratio; Republic of Korea; saving for education; saving for marriage; saving rate; sex ratio; son preference; wedding expenses